Improving Government Effectiveness: Analysis of the Implementation of the Electronic-Based Government System (SPBE) in Sarolangun Regency - Riska Afriyanti; Sofjan Aripin; Rahmat Budiman (Golden Ratio of Social Science and Education, 2026)
The objective of this study is to analyze the implementation of the Electronic-Based Government System (SPBE) policy in Sarolangun Regency, Jambi Province. This policy is one of the government's initiatives to enhance the effectiveness of governance through the use of information technology. Since the issuance of Sarolangun Regent Regulation No. 58 of 2020 concerning the Implementation of the Electronic-Based Government System, the Sarolangun Regency Government has encountered numerous impediments in its implementation, resulting in suboptimal execution of the Electronic-Based Government System. The present study employs a qualitative approach, drawing on data from interviews, observations, and documentation. The results of the study indicate that the implementation of SPBE in Sarolangun Regency continues to face challenges in communication and resource allocation. Several factors, including limited ICT infrastructure, a shortage of skilled human resources, insufficient socialization of digital services, and limited internet access, have hindered the implementation of this policy. The Sarolangun Regency Government, through the Sarolangun Regency Communication and Information Agency, must strengthen and improve resources and enhance communication to optimize the implementation of SPBE in Sarolangun Regency.